Wear-resistant high-entropy alloy with heterogeneous grain and heterogeneous phase structures
By introducing heterogeneous grains and heterogeneous phase structures into high-entropy alloys, combined with oxygen-containing mechanical alloying and discharge plasma sintering technology, the problem of difficulty in taking into account strength, toughness and wear resistance under high temperature conditions is solved, and high performance is achieved anti-wear high entropy alloy.
Patent Information
- Application Number
- CN202411688992.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-25
AI Technical Summary
It is difficult for existing high-entropy alloys to take into account strength, toughness and wear resistance at high temperatures, and the metallurgical incompatibility and stability between solid lubricants and metal matrix are insufficient, resulting in increased wear.
By introducing heterogeneous grains and heterogeneous phase structures into high-entropy alloys, using oxygen-containing mechanical alloying and discharge plasma sintering technology, heterogeneous interfaces and component fluctuations in multi-main solid solution are formed, and the grain boundaries are stabilized by combining B-element. , realize biheterogeneous precipitation and bimodal grain size distribution.
It achieves the maintenance of high compression strength and plastic strain over a wide temperature range, while significantly improving the stability of wear rate, ensuring excellent wear resistance of the material from room temperature to 1000 °C.
Smart Images

Figure CN119464886A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of high-performance high-temperature wear-resistant alloy materials, and in particular to a wear-resistant high-entropy alloy having both heterogeneous grains and heterogeneous phase structures. Background Art
[0002] In modern industry, especially in the fields of aerospace, energy and defense, mechanical parts often operate in high temperature environments. The wear problem of metal materials under high temperature conditions has become one of the key factors restricting their service life and performance. In the prior art, the wear of the metal material surface is mainly caused by thermal softening and friction oxidation, which causes the generated brittle oxide debris to crack and peel off easily, thereby aggravating the degree of wear. Although some oxide glaze layers can improve sliding friction through hardening and lubrication under certain conditions, the glaze layer often has problems of peeling and adhesive wear under high contact stress, resulting in limited wear resistance (Rasearch 2023;6:0160). To address this problem, the prior art usually uses solid lubricants (such as layered two-dimensional materials, metal fluorides and metal inorganic acid salts) to improve the friction performance of materials at high temperatures (TribologyInternational 2019;133:206-223). However, there is metallurgical incompatibility between solid lubricants and metal matrices, which can easily lead to a decrease in the mechanical properties of the alloy. In addition, solid lubricants are not stable enough under high temperature and high load conditions, and the failure of lubrication will accelerate the shedding and wear of the glaze layer. Therefore, at present, improving the wear resistance of materials through adaptive regulation of their microstructure under high temperature conditions is still a technical problem that needs to be solved urgently.
[0003] In recent years, high entropy alloys (also known as multi-principal alloys or chemically complex alloys) have gradually become a new type of material that breaks through the performance bottleneck of traditional alloys due to their unique high entropy effect and multi-principal component design (Science 2024;384:1017-1022; Nature 2022;602:251-257). High entropy alloys tend to form complex solid solution structures rather than traditional intermetallic compounds, and therefore exhibit good strength-toughness matching, thermal stability and wear resistance. By regulating the intrinsic or additional heterogeneous structures in the high entropy alloy system, the problems of strength-ductility trade-off and decreased wear resistance of traditional metal materials at high temperatures can be effectively solved. Currently, heterogeneous structures at various scales have been developed in high-entropy alloy systems, including: (i) chemical order at the local atomic level; (ii) indistinguishable nanoclusters or composites embedded in the matrix; (iii) precipitates, layered eutectics, and martensite induced by composition segregation; (iv) lattice defects such as twins, stacking faults, and grain boundaries; and (v) gradient grain size distribution from nanoscale to microscale (Nature Communications 2019;10:5623). Among them, heterogeneous precipitates are a particularly effective strengthening mechanism, which can not only regulate the nucleation and propagation of dislocations during deformation, but also affect the tribochemical reactions occurring during wear by introducing composition fluctuations and establishing secondary phase interfaces in the multi-component solid solution matrix (Journal of Materials Science&Technology 2023;153:75-91).
[0004] However, there are still some challenges in designing and introducing ideal anti-wear heterostructures in existing high entropy alloy systems. First, according to the Hertz contact model, the friction contact stress decreases with depth, resulting in a large strain gradient, which may amplify the local shear instability of the heterostructure during deformation and increase wear. Second, the existing methods of inducing precipitation phases and heterostructures (such as complex heat treatment processes, surface mechanical grinding, etc.) still have great limitations in microstructure regulation and friction load bearing capacity, and it is difficult to simultaneously take into account the coordinated development of strength, toughness and wear resistance. In addition, based on the physicochemical properties of the multi-principal solid solution matrix, it is extremely difficult to simultaneously introduce heterogeneous phase precipitation and bimodal grain distribution. On the one hand, heterogeneous phase precipitation often consumes the second phase nucleation elements in the alloy system, inhibiting the extensive dynamic recrystallization in the initial grains; on the other hand, the bimodal grain size distribution may lead to uneven precipitation of the precipitated phase, thereby significantly reducing the overall performance of the material.
[0005] In summary, it is of great significance to develop low-cost and process-efficient design strategies to simultaneously introduce heterogeneous grain and phase structures in high-entropy alloy systems that are sufficient to resist extreme wear conditions (wide temperature range and GPa-level Hertzian contact stress). Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a wear-resistant high-entropy alloy with low cost and reliable performance and having both heterogeneous grains and heterogeneous phase structures.
[0007] In order to solve the above problems, the present invention discloses a wear-resistant high-entropy alloy having both heterogeneous grains and heterogeneous phase structures, characterized in that: the high-entropy alloy is a single-phase high-entropy alloy, and its schematic chemical composition formula is H 95~85 P 3~13 B2, the ratio of each element is in atomic percentage; H represents a non-equiatomic chemical complex solid solution, which is (Co 25 Ni 23 Cr 20 Fe 20 ), (Cr 29 Fe 27 Ni 32 Nb6) or (Co 39 Ni 35 Nb 14 ) any one of them; P represents the heterogeneous precipitation nucleation composition, which is any one of (MoW), (TiV) or (TiAl); B is the grain boundary stabilizing element boron.
[0008] The method for preparing the wear-resistant high-entropy alloy having both heterogeneous grains and heterogeneous phase structures as described above comprises the following steps: (1) Co powder, Ni powder, Cr powder, Fe powder, Nb powder, Ti powder, Al powder, V powder, Mo powder, W powder and B powder are weighed according to a preset atomic ratio and put into a planetary high-energy ball mill, and dry-milled and alloyed under atmospheric conditions to obtain a dry supersaturated high-entropy solid solution powder; (2) adding 5% by weight of ethyl acetate to the dried supersaturated high entropy solid solution powder as a process control agent, placing the powder in a planetary ball mill again, and performing wet grinding and crystallization under the condition that the protective gas is argon to obtain a wet ultrafine crystal powder precursor; (3) placing the wet ultrafine-grained powder precursor in a vacuum oven at 65° C. and drying it to a constant weight, and then sieving it to obtain a pre-alloyed high-entropy solid solution powder with a particle size in the range of 1 to 20 μm; (4) The pre-alloyed high entropy solid solution powder is formed by spark plasma sintering to obtain a wear-resistant high entropy alloy having both heterogeneous grains and heterogeneous phase structures.
[0009] In the step (1), the Co powder, Ni powder, Cr powder, Fe powder, Nb powder, Ti powder, Al powder, V powder, Mo powder and W powder are all spherical or irregular in shape, with a particle size of 10-35 μm and a purity of >99.9%.
[0010] The particle size of the B powder in step (1) is 500 nm and the purity is >99.9%.
[0011] The conditions for the dry grinding alloying treatment in step (1) are to use carbide balls with a diameter of 5 to 15 mm as grinding balls, a ball-to-material ratio of 4 to 6:1, a rotation speed of 150 to 250 r / min, and a running time of 15 to 45 h.
[0012] The wet grinding and fine crystallization conditions in step (2) are as follows: using cemented carbide balls with a diameter of 5 to 15 mm as grinding balls, a ball-to-material ratio of 1.5 to 2.5:1, a rotation speed of 100 to 200 r / min, and a running time of 3 to 8 h.
[0013] The conditions for the spark plasma sintering in step (4) are as follows: the vacuum degree is less than 1 Pa, the sintering temperature is 1100-1250°C, the applied pressure is 30-40 MPa, and the holding time is 8-15 min.
[0014] The heating process in the spark plasma sintering molding in step (4) refers to a heating rate of 40-60°C / min from room temperature to 700°C, and a heating rate of 80-100°C / min from 700°C to 1100-1250°C.
[0015] Compared with the prior art, the present invention has the following advantages: 1. Based on the design concept of high strength-toughness matching and wear-resistant heterogeneous structure, the present invention simultaneously introduces heterogeneous phase precipitation and dynamic bimodal grain size distribution in multi-principal chemical complex solid solution through oxygen-containing mechanical alloying process combined with spark plasma sintering technology, and obtains high-performance heterogeneous high-entropy alloy: (1) A chemically complex matrix with high mixing entropy and near-zero mixing enthalpy is prepared by controlling the element ratios in (CoNiCrFe), (CrFeNiNb) or (CoNiNb) to ensure that the alloy matrix has high temperature stability and high solubility limit; (2) Inducing the second phase precipitation and continuous dynamic recrystallization of the multi-principal solid solution during the solid phase diffusion process through the second phase auxiliary nucleating agent (MoW), (TiV) or (TiAl), thereby driving the formation of heterogeneous interfaces and composition fluctuations; ⑶ Stabilize the grain boundaries by doping B elements and reduce the residual stress at the heterogeneous grain interfaces; (4) The thermal diffusion driven by Joule heat during oxygen-containing alloying and spark plasma sintering is used to make the supersaturated solid solution maintain a metastable composite solid solution state with dual heterogeneous precipitation and bimodal grain size distribution.
[0016] 2. The wear-resistant high-entropy alloy with both heterogeneous grains and heterogeneous phase structures of the present invention has a multi-principal component solid solution structure strengthened by double heterogeneous precipitation, and the grains are composed of graded grain regions with grain sizes greater than and less than 1 micron (initial grains and dynamic recrystallization regions), and the constituent elements undergo a wide range of composition fluctuations with the spatial distribution of the heterogeneous structure, and there are no sintering structural defects such as microcracks and pores inside the material.
[0017] 3. According to the test, the wear-resistant high entropy alloy with heterogeneous grains and heterogeneous phase structures has a compressive yield strength of not less than 1.4 GPa at room temperature, an ultimate compressive strength of not less than 1.9 GPa, and a plastic strain of not less than 12%; the compressive yield strength at 600 °C is not less than 1.0 GPa, the ultimate compressive strength is not less than 1.3 GPa, and the plastic strain is not less than 20%; at the same time, it exhibits excellent wide temperature range wear resistance, and its wear rate can be stably maintained at 10 in a wide temperature range from room temperature to 1000 °C. - 5 mm 3 / Nm order of magnitude.
[0018] 4. The present invention has a simple preparation process, low raw material cost, and high performance reliability, and has important application prospects in the wear resistance and load-bearing of motion / transmission parts of advanced mechanical systems in the fields of automobiles, energy, and aerospace. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.
[0020] Figure 1 The Co obtained by spark plasma sintering in Example 1 of the present invention is 25 Ni 23 Cr 20 Fe 20 XRD diffraction pattern of Ti6Al4B2 high entropy alloy (left) and corresponding 3D micro CT image (right).
[0021] Figure 2 The Co prepared in Example 1 of the present invention 25 Ni 23 Cr 20 Fe 20 TEM image of Ti6Al4B2 high entropy alloy (a) and corresponding EDS composition distribution (b).
[0022] Figure 3 Co prepared in Example 1 of the present invention 25 Ni 23 Cr 20 Fe 20 Compressive engineering stress-strain curves of Ti6Al4B2 from room temperature to high temperature.
[0023] Figure 4 Co prepared in Example 1 of the present invention 25 Ni 23 Cr 20 Fe 20 Wear rate of Ti6Al4B2 high entropy alloy at room temperature, 400 ℃, 600 ℃, 800 ℃ and 1000 ℃ test temperatures.
[0024] Figure 5 The Cr prepared by (a) the original powder in Example 2 of the present invention, the pre-alloyed powder by oxygen-containing high-energy ball milling and spark plasma sintering 29 Fe 27 Ni 32 XRD pattern of Nb6Ti2V2B2 high entropy alloy, and (b) EBSD grain orientation distribution map of sintered bulk sample. DETAILED DESCRIPTION
[0025] A wear-resistant high-entropy alloy having both heterogeneous grains and heterogeneous phase structures, wherein the high-entropy alloy is a single-phase high-entropy alloy, and its schematic chemical composition formula is H 95~85 P 3~13 B2, the ratio of each element is in atomic percentage; H represents a non-equiatomic chemical complex solid solution, which is (Co 25 Ni 23 Cr 20 Fe 20 ), (Cr 29 Fe 27 Ni 32 Nb6) or (Co 39 Ni 35 Nb 14 ) any one of them; P represents the heterogeneous precipitation nucleation composition, which is any one of (MoW), (TiV) or (TiAl); B is the grain boundary stabilizing element boron.
[0026] The preparation method thereof comprises the following steps: ⑴ Co powder, Ni powder, Cr powder, Fe powder, Nb powder, Ti powder, Al powder, V powder, Mo powder, W powder and B powder were weighed according to the preset atomic ratio and put into a planetary high-energy ball mill. Under atmospheric conditions, carbide balls with a diameter of 5-15 mm were used as grinding balls. The ball-to-material ratio (g / g) was 4-6:1 and the rotation speed was 150-250 r / min for dry grinding and alloying treatment. The operation was carried out for 15-45 h to obtain a dry supersaturated high-entropy solid solution powder.
[0027] Among them: Co powder, Ni powder, Cr powder, Fe powder, Nb powder, Ti powder, Al powder, V powder, Mo powder and W powder are all spherical or irregular in shape, with a particle size of 10~35 μm and a purity of >99.9%.
[0028] The particle size of B powder is 500 nm and the purity is >99.9%.
[0029] (2) Add 5% by mass of ethyl acetate to the dry supersaturated high entropy solid solution powder as a process control agent, put it into the planetary ball mill again, and use carbide balls with a diameter of 5-15 mm as grinding balls under the condition of argon as the protective gas, a ball-to-material ratio (g / g) of 1.5-2.5:1, and a rotation speed of 100-200 r / min for wet grinding and crystallization. Run for 3-8 hours to obtain a wet ultrafine crystal powder precursor.
[0030] ⑶ Place the wet ultrafine-grained powder precursor in a vacuum oven and dry it at 65°C to constant weight, then sieve it to obtain a pre-alloyed high-entropy solid solution powder with a particle size in the range of 1 to 20 μm.
[0031] (4) The pre-alloyed high entropy solid solution powder is formed by spark plasma sintering to obtain a wear-resistant high entropy alloy having both heterogeneous grains and heterogeneous phase structures.
[0032] Among them: the conditions for spark plasma sintering molding refer to vacuum degree less than 1 Pa, sintering temperature 1100~1250 ℃, applied pressure 30~40 MPa, and holding time 8~15min. The heating process refers to the heating rate from room temperature to 700 ℃ is 40~60 ℃ / min, and the heating rate from 700 ℃ to 1100~1250 ℃ is 80~100 ℃ / min.
[0033] Example 1 Preparation of Co 25 Ni 23 Cr 20 Fe 20 Ti6Al4B2 high entropy alloy: ⑴ Dry grinding alloying process: Co powder, Ni powder, Cr powder, Fe powder, Ti powder, Al powder and B powder were mixed according to the ratio shown in Table 1, weighed using an electronic balance and put into a planetary ball mill. Tungsten carbide alloy balls with a diameter of 5-15 mm were used as grinding balls. The ball-to-material ratio (g / g) was 4:1, the rotation speed was 200 r / min, and dry grinding alloying was carried out under atmospheric environment conditions. The running time was 32 h to obtain a dry supersaturated high entropy solid solution powder.
[0034] Table 1: Alloy raw material ratio (mass ratio wt.%) (2) Wet grinding and crystallization process: Add 5% of ethyl acetate by mass to the dry supersaturated high entropy solid solution powder as a process control agent, put it into the planetary ball mill again, use carbide balls with a diameter of 5-15 mm as grinding balls, the ball-to-material ratio (g / g) is 1.5:1, the rotation speed is 100 r / min, and run for 3 hours under the condition of argon protective gas to obtain a wet ultrafine crystal powder precursor.
[0035] ⑶ Drying: Place the wet ultrafine-grained powder precursor in a vacuum oven and dry it at 65°C until constant weight, then sieve it to obtain a pre-alloyed high-entropy solid solution powder with a particle size in the range of 1 to 20 μm.
[0036] ⑷Put the pre-alloyed high entropy solid solution powder before sintering into a graphite mold (φ30 mm or φ52 mm) surrounded by graphite paper, place it in a spark plasma sintering furnace, and start sintering at a preset constant pressure of 35 MPa. Sintering parameters: vacuum degree is less than 1 Pa, sintering temperature is 1200 ℃, holding time is 8 min, heating rate from room temperature to 700 ℃ is 50 ℃ / min, and heating rate from 700 ℃ to 1200 ℃ is 90 ℃ / min. After sintering, cool it to room temperature with the furnace to obtain Co with both wear-resistant heterogeneous grains and phase structure. 25 Ni 23 Cr 20 Fe 20 Ti6Al4B2 high entropy alloy.
[0037] The obtained sintered block samples were characterized by XRD diffraction and 3D micro-CT, such as Figure 1 The results show that after spark plasma sintering, Cr2B type and Al2O3 type heterogeneous second phases are precipitated in the multi-principal FCC matrix phase, proving the existence of component segregation during the sintering process. At the same time, the results show that the nanoprecipitates (red area) are evenly distributed throughout the sample, with a volume fraction of up to 42%, and no defects are observed. In addition, the high XRD diffraction peak intensity of the bulk alloy sample indicates that the sample prepared by the present invention has high purity and crystallinity.
[0038] The obtained sintered block was processed into a TEM test slice by FIB technology and then TEM characterization was performed, such as Figure 2 The results show that the sample has a heterogeneous bimodal grain size distribution. Figure 2 a) shows a high density of nanoprecipitates embedded in the gradient grains, with sizes ranging from tens to hundreds of nanometers. High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) and energy dispersive spectroscopy (EDS) mapping ( Figure 2b) shows that the heterogeneous structure contains (Ti, O)-rich nanoprecipitates (about 39 volume %), as well as (Cr, O)-rich (<2 volume %) and (Al, O)-rich (about 5 volume %) phases, in which oxygen is incorporated during the mechanical alloying process. Combined XRD and TEM analysis shows that the present invention successfully prepared a wear-resistant high-entropy alloy with both heterogeneous grains and heterogeneous phase structures.
[0039] The obtained bulk single-phase high entropy alloy was machined into a φ3×6 mm cylindrical compression sample and polished with 2000 mesh metallographic sandpaper. The WDW-200 material mechanical testing machine was used to test the material at 5 × 10 -4 s -1 The compression performance of the compression sample was tested from room temperature to 1000 °C at a strain rate of 1000 °C, and the test was repeated at least three times. Figure 3 As shown in the figure, at room temperature, the high entropy alloy material exhibits a yield strength of 1.8 GPa, an ultimate compressive strength of 2.3 GPa, and a fracture strain of 13%. At 600°C, the yield strength remains at 1.4 GPa, the ultimate compressive strength is 1.6 GPa, and the fracture strain increases to 20%. As the temperature further increases, the yield strength drops to 408 MPa at 800°C and to 105 MPa at 1000°C, and above 800°C, the fracture strain exceeds 40%. This shows that the Co prepared by the present invention 25 Ni 23 Cr 20 Fe 20 Ti6Al4B2 high entropy alloy exhibits excellent strength-toughness matching over a wide temperature range.
[0040] The obtained bulk single-phase high-entropy alloy was machined into a φ15 × 3 mm cylindrical sample and polished with metallographic sandpaper. The surface roughness of the sample was 20 nm. The wear performance was tested using a HT-1000 ball-disc commercial high-temperature friction machine. The pair was a Si3N4 ceramic ball (hardness of approximately 15 GPa), the test distance was 360 m, the Hertzian contact stress was approximately 1.2 GPa, and the sliding speed was 0.2 m / s; the test temperature was set to room temperature, 400 ℃, 600 ℃, 800 ℃, and 1000 ℃. After the test, the MicroXAM-800 non-contact three-dimensional profiler was used to test the wear rate of the sample, where the wear rate is measured by the ratio of the wear volume to the product of the sliding distance and the applied load. Figure 4 As shown in Figure 2, the wear rate of the single-phase high entropy alloy is stably maintained at (0.2~3.5) × 10 -5 mm 3 / Nm order of magnitude. Experimental results show that Co 25 Ni 23 Cr20 Fe 20 Ti6Al4B2 high entropy alloy has excellent wear resistance over a wide temperature range.
[0041] Example 2 Preparation of Cr 29 Fe 27 Ni 32 Nb6Ti2V2B2 high entropy alloy: (1) Dry grinding alloying process: Cr powder, Fe powder, Ni powder, Nb powder, Ti powder, V powder and B powder were mixed according to the ratio shown in Table 2, weighed using an electronic balance and put into a planetary ball mill. Tungsten carbide alloy balls with a diameter of 5-15 mm were used as grinding balls. The ball-to-material ratio (g / g) was 5:1, the rotation speed was 150 r / min, and dry grinding alloying was carried out under atmospheric conditions for 45 h to obtain a dry supersaturated high entropy solid solution powder.
[0042] Table 2: Alloy raw material ratio (mass ratio wt.%) (2) Wet grinding and crystallization process: Add 5% of ethyl acetate by mass to the dry supersaturated high entropy solid solution powder as a process control agent, put it into the planetary ball mill again, use carbide balls with a diameter of 5-15 mm as grinding balls, a ball-to-material ratio (g / g) of 2:1, a rotation speed of 150 r / min, and run for 6 hours under the condition of argon protective gas to obtain a wet ultrafine crystal powder precursor.
[0043] ⑶ Drying: Place the wet ultrafine-grained powder precursor in a vacuum oven and dry it at 65°C until constant weight, then sieve it to obtain a pre-alloyed high-entropy solid solution powder with a particle size in the range of 1 to 20 μm.
[0044] The obtained initial raw material powder and pre-alloyed high entropy solid solution powder were characterized by XRD, such as Figure 5 As shown in (a), obvious peaks corresponding to all elements can be observed in the raw powder sample; after high-energy ball milling, the intensity of most diffraction characteristic peaks weakened, and the peaks of some alloy elements (Ti, V) disappeared, indicating that mutual dissolution occurred between the constituent elements. In contrast, the peaks of Cr, Fe and Ni are more obvious. This shows that the alloy elements are partially dissolved in the matrix to form a supersaturated multi-component solid solution. In addition, due to local lattice distortion, the half-peak width of the diffraction peak increases with the extension of ball milling time. The alloyed powders are composed of FCC and several BCC solid solutions.
[0045] ⑷Put the pre-alloyed high entropy solid solution powder before sintering into a graphite mold (φ30 mm or φ52 mm) surrounded by graphite paper, place it in a spark plasma sintering furnace, and start sintering at a preset constant pressure of 30 MPa. Sintering parameters: vacuum degree is less than 1 Pa, sintering temperature is 1100 ℃, holding time is 12 min, heating rate from room temperature to 700 ℃ is 60 ℃ / min, and heating rate from 700 ℃ to 1100 ℃ is 80 ℃ / min. After sintering, cool it to room temperature with the furnace to obtain Cr with both wear-resistant heterogeneous grains and phase structure. 29 Fe 27 Ni 32 Nb6Ti2V2B2 high entropy alloy.
[0046] The obtained sintered block samples were characterized by XRD diffraction, such as Figure 5 (a) shows that after sintering, the crystallinity of the sample is improved. The high entropy alloy contains a main matrix phase and two heterogeneous phases. Among them, the matrix phase is a (Fe, Ni) type FCC solid solution, and the heterogeneous phase includes boride and oxide phases with NiB type and Ni2Ti4O type structures. Combined with XRD and EBSD analysis, it is shown that the present invention successfully prepared a wear-resistant high entropy alloy with both heterogeneous grains and heterogeneous phase structures.
[0047] Example 3 Preparation of Cr 29 Fe 27 Ni 32 Nb6Mo2W2B2 high entropy alloy: ⑴ Dry grinding alloying process: Cr powder, Fe powder, Ni powder, Nb powder, Mo powder, W powder and B powder were mixed according to the ratio shown in Table 3, weighed using an electronic balance and put into a planetary ball mill. Tungsten carbide alloy balls with a diameter of 5-15 mm were used as grinding balls. The ball-to-material ratio (g / g) was 6:1, the rotation speed was 250 r / min, and dry grinding alloying was carried out under atmospheric conditions for 20 h to obtain a dry supersaturated high entropy solid solution powder.
[0048] Table 3: Alloy raw material ratio (mass ratio wt.%) (2) Wet grinding and crystallization process: Add 5% of ethyl acetate by mass to the dry supersaturated high entropy solid solution powder as a process control agent, put it into the planetary ball mill again, use carbide balls with a diameter of 5-15 mm as grinding balls, the ball-to-material ratio (g / g) is 2.5:1, the rotation speed is 200 r / min, and run for 8 h under the condition of argon protective gas to obtain a wet ultrafine crystal powder precursor.
[0049] ⑶ Drying: Place the wet ultrafine-grained powder precursor in a vacuum oven and dry it at 65°C until constant weight, then sieve it to obtain a pre-alloyed high-entropy solid solution powder with a particle size in the range of 1 to 20 μm.
[0050] ⑷Put the pre-alloyed high entropy solid solution powder before sintering into a graphite mold (φ30 mm or φ52 mm) surrounded by graphite paper, place it in a spark plasma sintering furnace, and start sintering at a preset constant pressure of 40 MPa. Sintering parameters: vacuum degree is less than 1 Pa, sintering temperature is 1250 ℃, holding time is 15 min, heating rate from room temperature to 700 ℃ is 40 ℃ / min, and heating rate from 700 ℃ to 1250 ℃ is 100 ℃ / min. After sintering, cool it to room temperature with the furnace to obtain Cr with both wear-resistant heterogeneous grains and phase structure. 29 Fe 27 Ni 32 Nb6Mo2W2B2 high entropy alloy.
[0051] Example 4 Preparation of Co 39 Ni 35 Nb 14 Ti6Al4B2 high entropy alloy: ⑴ Dry grinding alloying process: Co powder, Ni powder, Nb powder, Ti powder, Al powder and B powder were mixed according to the ratio shown in Table 4, weighed using an electronic balance and put into a planetary ball mill. Tungsten carbide alloy balls with a diameter of 5-15 mm were used as grinding balls. The ball-to-material ratio (g / g) was 4.5:1, the rotation speed was 250 r / min, and dry grinding alloying was carried out under atmospheric conditions for 15 h to obtain a dry supersaturated high entropy solid solution powder.
[0052] Table 4: Alloy raw material ratio (mass ratio wt.%) (2) Wet grinding and crystallization process: Add 5% of ethyl acetate by mass to the dry supersaturated high entropy solid solution powder as a process control agent, put it into the planetary ball mill again, use carbide balls with a diameter of 5-15 mm as grinding balls, a ball-to-material ratio (g / g) of 2:1, a rotation speed of 150 r / min, and run for 6 hours under the condition of argon protective gas to obtain a wet ultrafine crystal powder precursor.
[0053] ⑶ Drying: Place the wet ultrafine-grained powder precursor in a vacuum oven and dry it at 65°C until constant weight, then sieve it to obtain a pre-alloyed high-entropy solid solution powder with a particle size in the range of 1 to 20 μm.
[0054] ⑷Put the pre-alloyed high entropy solid solution powder before sintering into a graphite mold (φ30 mm or φ52 mm) surrounded by graphite paper, place it in a spark plasma sintering furnace, and start sintering at a preset constant pressure of 40 MPa. Sintering parameters: vacuum degree is less than 1 Pa, sintering temperature is 1135 ℃, holding time is 10 min, heating rate from room temperature to 700 ℃ is 55 ℃ / min, and heating rate from 700 ℃ to 1135 ℃ is 95 ℃ / min. After sintering, cool it to room temperature with the furnace to obtain Co with both wear-resistant heterogeneous grains and phase structure. 39 Ni 35 Nb 14 Ti6Al4B2 high entropy alloy.
Claims
1. A wear-resistant high-entropy alloy having both heterogeneous grains and heterogeneous phase structures, characterized in that: The high entropy alloy is a single-phase high entropy alloy, and its schematic chemical composition formula is H 95~85 P 3~13 B2, the ratio of each element is in atomic percentage; H represents a non-equiatomic chemical complex solid solution, which is (Co 25 Ni 23 Cr 20 Fe 20 ), (Cr 29 Fe 27 Ni 32 Nb6) or (Co 39 Ni 35 Nb 14 ) any one of them; P represents the heterogeneous precipitation nucleation composition, which is any one of (MoW), (TiV) or (TiAl); B is the grain boundary stabilizing element boron.
2. A method for preparing a wear-resistant high-entropy alloy having both heterogeneous grains and heterogeneous phase structures as claimed in claim 1, comprising the following steps: (1) Co powder, Ni powder, Cr powder, Fe powder, Nb powder, Ti powder, Al powder, V powder, Mo powder, W powder and B powder are weighed according to a preset atomic ratio and put into a planetary high-energy ball mill, and dry-milled and alloyed under atmospheric conditions to obtain a dry supersaturated high-entropy solid solution powder; (2) adding 5% by weight of ethyl acetate to the dried supersaturated high entropy solid solution powder as a process control agent, placing the powder in a planetary ball mill again, and performing wet grinding and crystallization under the condition that the protective gas is argon to obtain a wet ultrafine crystal powder precursor; (3) placing the wet ultrafine-grained powder precursor in a vacuum oven at 65° C. and drying it to a constant weight, and then sieving it to obtain a pre-alloyed high-entropy solid solution powder with a particle size in the range of 1 to 20 μm; (4) The pre-alloyed high entropy solid solution powder is formed by spark plasma sintering to obtain a wear-resistant high entropy alloy having both heterogeneous grains and heterogeneous phase structures.
3. The method for preparing a wear-resistant high-entropy alloy having both heterogeneous grains and heterogeneous phase structures as claimed in claim 2, characterized in that: In the step (1), the Co powder, Ni powder, Cr powder, Fe powder, Nb powder, Ti powder, Al powder, V powder, Mo powder and W powder are all spherical or irregular in shape, with a particle size of 10-35 μm and a purity of >99.9%.
4. The method for preparing a wear-resistant high-entropy alloy having both heterogeneous grains and heterogeneous phase structures as claimed in claim 2, characterized in that: The particle size of the B powder in step (1) is 500 nm and the purity is >99.9%.
5. The method for preparing a wear-resistant high-entropy alloy having both heterogeneous grains and heterogeneous phase structures as claimed in claim 2, characterized in that: The conditions for the dry grinding alloying treatment in step (1) are to use carbide balls with a diameter of 5 to 15 mm as grinding balls, a ball-to-material ratio of 4 to 6:1, a rotation speed of 150 to 250 r / min, and a running time of 15 to 45 h.
6. The method for preparing a wear-resistant high-entropy alloy having both heterogeneous grains and heterogeneous phase structures as claimed in claim 2, characterized in that: The wet grinding and fine crystallization conditions in step (2) are as follows: using cemented carbide balls with a diameter of 5 to 15 mm as grinding balls, a ball-to-material ratio of 1.5 to 2.5:1, a rotation speed of 100 to 200 r / min, and a running time of 3 to 8 h.
7. The method for preparing a wear-resistant high-entropy alloy having both heterogeneous grains and heterogeneous phase structures as claimed in claim 2, characterized in that: The conditions for spark plasma sintering in step (4) are as follows: vacuum degree is less than 1 Pa, sintering temperature is 1100-1250°C, applied pressure is 30-40 MPa, and holding time is 8-15 min.
8. The method for preparing a wear-resistant high-entropy alloy having both heterogeneous grains and heterogeneous phase structures as claimed in claim 2, characterized in that: The heating process in the spark plasma sintering molding in step (4) refers to a heating rate of 40-60 °C / min from room temperature to 700 °C, and a heating rate of 80-100 °C / min from 700 °C to 1100-1250 °C.
Citation Information
Patent Citations
Medium-entropy alloy with high strength and high wear resistance and preparation method thereof
CN112647009A
Single-phase high-entropy alloy with micron / nano crystal grain composite structure
CN114293087A
High entropy multicomponent alloy
JP2002173732A
Invading sensing system using position analisis by composite cable occuring magnetic induction signal, microwave signal, electris chagre and optical signal
KR1020240142710A
Cited By
Three-dimensional network distribution gradient grain structure high-entropy alloy and preparation method thereof
CN120533106A